Application of the Geogebra Assisted Problem-Based Learning Model to Increase Student Activity and Learning Outcomes - Carli (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This research is motivated by the low level of activity and student learning outcomes in mathematics at MTsN 3 Kota Tangerang. This can be seen from the students' difficulties in solving math HOTS questions. One of the causes of this is the not yet optimal application of innovative learning models, where teachers still dominate the activity in learning activities in class, so that students still have difficulties in conducting investigations of abstract concepts. Therefore, the Geogebra application is needed to concretize abstract mathematical concepts and attract students' interest in learning mathematics. The purpose of this study was to determine the increase in the activity and learning outcomes of SMP/MTs students by using problem-based learning assisted by the Geogebra application. The method used in this research is a Quasy experimental research with one group pretest posttest design. Researchers took one class of six class VIII by means of random sampling. The sample of this research was 39 students of class VIII-1 MTs Negeri 3 Tangerang City. The research instrument was a matter of description and observation sheets of student activity. The results of the quasi-experimental research show that problem-based learning assisted by Geogebra can increase student activity and learning outcomes.